2020
DOI: 10.1111/cup.13666
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inflammatory features of central centrifugal cicatricial alopecia

Abstract: Central centrifugal cicatricial alopecia (CCCA) is a scarring alopecia that primarily affects women of African descent. Although histopathological features of CCCA have been described, the pathophysiology of this disease remains unclear. To better understand the components of CCCA pathophysiology, we evaluated the composition of the inflammatory infiltrate, the distribution of Langerhans cells (LCs), and the relationship between fibrosis and perifollicular vessel distribution. Our data indicate that CCCA is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…c. Central centrifugal cicatricial alopecia: Central centrifugal cicatricial alopecia (CCCA) is a type of scarring alopecia characterized by patches of permanent hair loss originating on the scalp vertex/ crown with centrifugal spread, associated with signs of inflammation (Flamm et al, 2020). CCCA is especially common among women of African descent (uncommon in men and children), with an average age of onset of 36 years (Malki et al, 2019).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
See 1 more Smart Citation
“…c. Central centrifugal cicatricial alopecia: Central centrifugal cicatricial alopecia (CCCA) is a type of scarring alopecia characterized by patches of permanent hair loss originating on the scalp vertex/ crown with centrifugal spread, associated with signs of inflammation (Flamm et al, 2020). CCCA is especially common among women of African descent (uncommon in men and children), with an average age of onset of 36 years (Malki et al, 2019).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…The pathophysiology of CCCA is not well established (possibly owing to a shortage of studies in the literature); however, several studies have suggested that processes leading to premature desquamation of the inner root sheath (PDIRS) are critical in CCCA pathogenesis (Flamm et al, 2020). One group observed that mutations in the PADI3 gene may be correlated with CCCA (Malki et al, 2019).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…10). 71 Histopathological features associated with CCCA include premature desquamation of the inner root sheath (IRS), compound follicular structures with perifollicular fibrosis and naked hair shafts with a foreign‐body inflammatory reaction in fibrous streamers 72 …”
Section: Cicatricial Hair Diseasesmentioning
confidence: 99%
“…Flamm et al recently described increased numbers of LCs extending into the lower hair follicle in central centrifugal cicatricial alopecia. [ 58 ] Enhanced LC/T lymphocyte ratios were reported in lichen planopilaris compared to traction alopecia, [ 59 ] while a loss of LCs in interfollicular epidermis was described in association with hair follicle destruction in lichen planopilaris and folliculitis decalvans. [ 60 ] Perifollicular and intrafollicular LCs appear to be increased in hair follicle affected the frontal fibrosing alopecia, [ 61 ] but most investigations are limited to immunohistochemical stainings of patient biopsies.…”
Section: Could Dysregulated Cross‐talk At This Interface Contribute Tmentioning
confidence: 99%